Beyond the gathering storm eaudiobook - Oke, Janette (Delaney Family, 2014)
Best-selling author Janette Oke, noted for vivid historical settings and heartwarming spiritual drama spins the tale of a close-knit family facing separation and change. Years ago, Wynn and Elizabeth Delaney adopted Christine and Henry. Now Christine has moved to a nearby city. Working as a secretary in a prosperous company, she is drawn to her employer's handsome son. Henry has joined the Canadian Mounties, where one of his first duties is to help a young widow and her infant. In their new lives, as new relationships grow, can Christine and Henry still draw on the faith they have learned from their parents?